Impact Of The Covid-19 Pandemic On Pregnant Mother's Anxiety: A Systematic Review - Zeni Zaenal Mutaqin (Science Midwifery, 2021)
The COVID-19 pandemic has impacted all aspects of life. Lockdown policies, poverty due to layoffs, and a lot of information about deaths have disrupted people's mental health. This study aims to prove the effect of the COVID-19 pandemic on the anxiety of pregnant women. The research method is a systematic review with 4 (four) stages of work: identification, screening, feasibility, and input. Search articles using three databases: Proquest, PubMed, and Google Sholar during the covid-19 pandemic period (2019-2021). The article is an English and Bahasa journal. The results of the study found 1,712 articles. After screening the eligibility criteria articles are 29 articles then reviewed. The results of the study show that the COVID-19 pandemic causes anxiety in pregnant women. The poverty factor makes the anxiety level higher. Special policies are needed for health services for pregnant women and economic support for families who have pregnant women.